Interoperability and open-source solutions for the internet of things : International Workshop, FP7 OpenIoT Project, held in conjunction with SoftCOM 2014, Split, Croatia, September 18, 2014, Invited papers /: International Workshop, FP7 OpenIoT Project, held in conjunction with SoftCOM 2014, Split, Croatia, September 18, 2014, Invited papers. (2015) - Unknown
No abstract available